Coffee, green tea, black tea and oolong tea consumption and risk of mortality from cardiovascular disease in Japanese men and women. Issue 3 (8th December 2009) - Mineharu, Yohei; Koizumi, Akio; Wada, Yasuhiko; Iso, Hiroyasu; Watanabe, Yoshiyuki; Date, Chigusa; Yamamoto, Akio; Kikuchi, Shogo; Inaba, Yutaka; Toyoshima, Hideaki; Kondo, Takaaki; Tamakoshi, Akiko; et al.
Abstract : Background: The effects of coffee and green, black and oolong teas and caffeine intake on cardiovascular disease (CVD) mortality have not been well defined in Asian countries. Methods: To examine the relationship between the consumption of these beverages and risk of mortality from CVD, 76 979 individuals aged 40–79 years free of stroke, coronary heart disease (CHD) and cancer at entry were prospectively followed. The daily consumption of beverages was assessed by questionnaires. Results: 1362 deaths were documented from strokes and 650 deaths from CHD after 1 010 787 person-years of follow-up. Compared with non-drinkers of coffee, the multivariable HR and 95% CI for those drinking 1–6 cups/week, 1–2 cups/day and ≥3 cups/day were 0.78 (0.50 to 1.20), 0.67 (0.47 to 0.96) and 0.45 (0.17 to 0.87) for strokes among men (p=0.009 for trend). Compared with non-drinkers of green tea, the multivariable HR for those drinking 1–6 cups/week, 1–2 cups/day, 3–5 cups/day and ≥6 cups/day were 0.34 (0.06–1.75), 0.28 (0.07–1.11), 0.39 (0.18–0.85) and 0.42 (0.17–0.88) for CHD among women (p=0.038 for trend). As for oolong tea, the multivariable HR of those drinking 1–6 cups/week and ≥1 cups/day were 1.00 (0.65–1.55) and 0.39 (0.17–0.88) for total CVD among men (p=0.049 for trend). Risk reduction for total CVD across categories of caffeine intake was most prominently observed in the second highest quintile, with a 38% lower risk among men and 22% among women. Conclusions: Consumption of coffee, green tea and oolong tea and total caffeine intake was associated with a reduced risk of mortality from CVD.